A formação de leitores por meio das narrativas mitológicas greco-romanas - Sette, Aline Teixeira Cavalcanti (2016)
Reading is essential to train an autonomous person, because enable the character to fully exercise their citizenship. Therefore, it is imputed to the school the role of making a character capable of read proficiently as well as rouse the interest of the student on the reading world. We believe that the literary texts gather all the attributes needed in order to obtain success in such tasks. It is capable to delight the reader and, with no doubt, contribute to his formation. Considering the importance of the reading, focusing on the literary object, we present in this research, of applied nature and interventionist, a work proposal with the subject myth, specifically, Greco – roman mythology. Thus, we are going to use the book “Histórias Greco-romanas” written by Ana Maria Machado. The Greco-roman mythological narrative have a significant cultural relevance in all over the world, until nowadays they are a recurrent theme in more diverse research areas and exerts notable fascination over the public, mostly the young public. Present in different languages, they are timeless and offer subsid to the comprehension of the human world, mind and human relationship.The main objective of this work is to propose literature as a way of awakening the taste and habit of reading and, as a result, increase the reading competence of students in the 7th grade of elementary school of a public school located in Recife. To enable this proposal, an interventional project was developed which included reading workshops, based on the proposal of Cosson (2014b). The theoretical support of this work is basically based in the studies of Grimal (1982) Cosson (2014th / b), Colomer (2007), Gregorin Filho (2011), Machado (2011), among others.